Assessing the Current Status of Renewable Energies and Their Limitations in Iran - Somayeh Pahlavan; Mehdi Jahangiri; Akbar Alidadi Shamsabadi; Alireza Baharizadeh (International Journal of Renewable Energy Development, 2020)
Innovative and more sustainable methods of supplying energy needs in the world have led to a change in the dependency model for fossil fuels, including more integrated planning and adoption of new and motivating models regarding the use of renewable energy. Today, with the reduction of fossil fuel consumption in the world, the use of renewable energy has gained an important role in the global energy mix, but according to studies, the share of renewable energy in Iran’s energy mix is very small. Therefore, the present paper attempts to present all potentialities for obtaining clean energy in Iran by assessing the current state of renewable energies. The fact that, in the present time, the real value of energy carriers is not appreciated properly in Iran, on the one hand, and the lack of willingness to invest in these energies in the private sector, which may have been less protected, on the other hand, has caused the consumption level of fossil fuels to remain unchanged, which may have some disadvantages, such as environmental damage, in addition to their utilization. The authors of the paper are of the opinion that, on the one hand, by finding solutions for bank investment problems, easing restrictive laws, providing bank with guarantees by investors, as well as modifying parts of the guaranteed electricity purchase contract for accepting foreign banks to provide loans and obtain financing, and on the other hand, by facilitating the process of obtaining land permits and connecting to these power plants, Iran is not far from reaching a reasonable rank in the world.©2020. CBIORE-IJRED. All rights reserved